2017
DOI: 10.1038/srep44077
|View full text |Cite
|
Sign up to set email alerts
|

Selective intracellular vaporisation of antibody-conjugated phase-change nano-droplets in vitro

Abstract: While chemotherapy is a major mode of cancer therapeutics, its efficacy is limited by systemic toxicities and drug resistance. Recent advances in nanomedicine provide the opportunity to reduce systemic toxicities. However, drug resistance remains a major challenge in cancer treatment research. Here we developed a nanomedicine composed of a phase-change nano-droplet (PCND) and an anti-cancer antibody (9E5), proposing the concept of ultrasound cancer therapy with intracellular vaporisation. PCND is a liquid perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 45 publications
0
30
0
Order By: Relevance
“…9E5 is an anti‐epiregulin (EREG) antibody that targets cell membrane–expressed ligands of epidermal growth factor receptors . Previously, we have demonstrated that 9E5‐conjugated PCNDs can be selectively introduced into tumor cells via receptor‐mediated endocytosis and that exposure to ultrasound‐induced intracellular vaporization leads to a rapid disruption of cellular structure . In the present study, we compared cytotoxicity due to vaporization inside and outside cells and demonstrated that intracellular delivery of PCNDs reduces ultrasound pressure for vaporization to induce cytotoxicity.…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…9E5 is an anti‐epiregulin (EREG) antibody that targets cell membrane–expressed ligands of epidermal growth factor receptors . Previously, we have demonstrated that 9E5‐conjugated PCNDs can be selectively introduced into tumor cells via receptor‐mediated endocytosis and that exposure to ultrasound‐induced intracellular vaporization leads to a rapid disruption of cellular structure . In the present study, we compared cytotoxicity due to vaporization inside and outside cells and demonstrated that intracellular delivery of PCNDs reduces ultrasound pressure for vaporization to induce cytotoxicity.…”
Section: Introductionmentioning
confidence: 67%
“…9E5 hybridoma cells were intraperitoneally implanted in BALB/c nude mice, and ascites were obtained and purified on a Protein G column. 9E5 monoclonal antibody was prepared and biotinylated as described previously . All animals were maintained in accordance with the regulations set by the University of Tokyo, and all animal experiments were conducted following institutional guidelines.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The conjugated antibody bound to epiregulin receptors, which are overexpressed on human colonic adenocarcinoma cell line DLD1 and caused 97.8 ± 0.5% accumulation of the nanoparticles into the DLD1 cells, which was significantly higher than the 1.4 ± 0.3% accumulation of the nanodroplets without the antibody. Furthermore, upon insonation, intracellular vaporization generated by the perfluorocarbon liquid in the nanodroplets killed 57% of the targeted DLD1 cells [110]. In a different approach, placental mesenchymal stem cells were used as cell-targeting vectors for the ultrasound-responsive nanoparticles into tumor cells.…”
Section: Ultrasound-responsive Nanomaterialsmentioning
confidence: 99%
“…(a) aptamer- and (b) antibody-conjugated ultrasound-responsive nanodroplets designed for tumor targeted therapy and their interaction with cancerous cells and subseqent degradation by ultrasound (Figures taken from references [109] and [110], respectively).…”
Section: Figurementioning
confidence: 99%